Is acupuncture effective in the treatment of pain in endometriosis? - Lund I; Lundeberg T (Journal of Pain Research, 2016)
Iréne Lund,1 Thomas Lundeberg21Department of Physiology and Pharmacology, Karolinska Institutet, 2Rehabilitation Medicine University Clinic Stockholm, Danderyds Hospital AB, Stockholm, SwedenIntroduction: Endometriosis is a multifactorial, estrogen-dependent, inflammatory gynecological condition – often with long-lasting visceral pelvic pain of different origin, and infertility among women. Current management options for patients’ are often inadequate, with side effects for many for whom acupuncture techniques could be an alternative. Earlier studies have discussed the efficacy of acupuncture, but not its methodological aspects.Objectives: To summarize the documented clinical effects of acupuncture on rated visceral pelvic endometriosis-related pain, and associated variables among individuals, within and between studied groups, and to discuss the methodological treatment aspects.Methods: Published full text clinical studies, case reports, and observational studies with abstracts written in English were searched by using the keywords “Acupuncture and Endometriosis” in databases such as PubMed, Web of Science, and CINAHL. The reporting guidelines, Standards for Reporting Interventions in Clinical Trials of Acupuncture was used for the methodological report.Results: Three studies were found including 99 women, 13–40 years old, with diagnosed endometriosis. The studies were different in research design, needle stimulation techniques, and evaluation instruments. Methodological similarities were seven to12 needle insertions per subject/session, and 15–25 minutes of needle retention time. The needles were placed in lower back/pelvic-abdominal area, in the shank, feet, and hands. Treatment numbers varied from nine to 16 and patients received one to two treatments per week. Similarity in reported treatment effects in the quoted studies, irrespective of research design or treatment technique, was reported decrease of rated pain intensity.Discussion: Meta-analysis is the standard procedure for the evaluation of evidence of treatment effects, ie, on a group level, usually without analysis of the individual responses even with obvious spread in the results leading to lack of guidance for treatment of the individual patient. By conceptualizing pain as subjective, the individual aspect should serve as the basis for the analysis to allow clinical recommendations. From a physiological and a western medical perspective, acupuncture can be regarded as a type of sensory stimulation that induces changes in the function of the central nervous system that partly can explain the decrease of perceived pain in response to acupuncture treatment irrespective of the technique.Conclusion: Endometriosis is often painful, although with various origin, where standard treatments may be insufficient or involve side effects. Based on the reported studies, acupuncture could be tried as a complement as it is an overall safe treatment. In the future, studies designed for evaluating effectiveness between treatment strategies rather than efficacy design would be preferred as the analyses of treatment effects in the individual patients.Keywords: acupuncture, endometriosis, pelvic pain, pain treatment, STRICTA, individual responses